2007
DOI: 10.1002/joc.1464
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tropical cyclones on Hainan Island's extreme and total precipitation

Abstract: Abstract:Total and extreme precipitation in Hainan Island was investigated in this study, based on consistent meteorological data for the period . Results show that tropical cyclones mainly impact Hainan Island between June and November, during which time they account for more than one-third of the total precipitation. Over the past four decades, the number of TCs impacting Hainan Island has significantly decreased. Correspondingly, the TC precipitation and its contribution to the total precipitation have slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 13 publications
(11 reference statements)
4
37
0
Order By: Relevance
“…6d). In agreement with Wu et al (2007), the increasing trend in the extreme rainfall per TC is statistically significant in southern Hainan Island. Note that the significant trends were calculated with a sample size of more than 30 TCs.…”
Section: Changes In the Average Rainfall Per Tcsupporting
confidence: 81%
See 1 more Smart Citation
“…6d). In agreement with Wu et al (2007), the increasing trend in the extreme rainfall per TC is statistically significant in southern Hainan Island. Note that the significant trends were calculated with a sample size of more than 30 TCs.…”
Section: Changes In the Average Rainfall Per Tcsupporting
confidence: 81%
“…Despite the obvious interannual and decadal variations in the annual TC rainfall, the upward trends can be clearly seen at these stations since the 1980s. Wu et al (2007) studied the impact of TC rainfall on Hainan Island during 1962̶2005 and showed that the rainfall amount and the number of days of extreme events related to each TC have been significantly increased, although the number of TCs that affected Hainan Island has significantly decreased over the past four decades due to the prevailing track shifts reported by Wu et al (2005). In this study, the extreme rainfall for each TC at a specific station is obtained by normalizing the annual extreme rainfall with the number of TCs affecting the station (Figs.…”
Section: Changes In the Average Rainfall Per Tcmentioning
confidence: 99%
“…For instance, Shephard et al [7] found that TCs accounted from 8 to 17% of cumulative rainfall during hurricane seasons at different locations along the coastal southeastern United States. Wu et al [8] pointed out that TCs produce more than one third of the total precipitation between June and November at Hainan Island in China. A TC that is close to the Pacific coast of Mexico may contribute from 20 to 60% of seasonal rainfall along coastal regions of Mexico, and up to 30% in landmass of western Mexico [9,10,11].…”
mentioning
confidence: 99%
“…In other words, more precipitation falls in a shorter period in the north, suggesting that more short-duration storms occur in this region. Wu et al [29] also found that the heaviest 1% of daily precipitation contributes 23% of the annual precipitation in Hainan Island. In our study, at least 80% of the total precipitation is found to fall in the 20% rainiest hours.…”
Section: Discussionmentioning
confidence: 95%
“…In line with IPCC findings [1], the frequency and intensity of extreme precipitation events was found to exhibit increasing trends corresponding with observed global warming. According to Wu et al [29], extreme events contribute significantly to variations in the extreme precipitation amount, as well as in the total annual precipitation. During the period from 1962 to 2005, both the number of days and the total precipitation associated with extreme events slightly increased in Hainan Island.…”
Section: Discussionmentioning
confidence: 99%